2007
DOI: 10.4141/p05-137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop rotation and soil amendments on Sclerotinia stem rot on soybean in two soils

Abstract: Rousseau, G., Rioux, S. and Dostaler D. 2007. Effect of crop rotation and soil amendments on Sclerotinia stem rot on soybean in two soils. Can. J. Plant Sci. 87: 605-614. The effect of 4-yr soybean rotations with corn (CCCS vs. CCSS vs. SSSS) and soil amendments (urban compost vs. mineral fertilizer) on Sclerotinia stem rot of soybean (disease severity index, apothecia number, sclerotia survival), caused by Sclerotinia sclerotiorum, was studied on two soils (clay loam and sandy loam) at SaintHyacinthe, in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…In general, the management of S. sclerotiorum borne disease is not much easy because of its widespread existence, irregular incidence, and the long-term survival by producing huge numbers of sclerotia in the soil. Although several control measures like chemical and cultural methods have been devised and adopted for countering the Sclerotinia stem rot menace (Rousseau et al, 2007) none of them were found fully effective in preventing either the process of disease infection or pathogenesis progression after infection. The extent of genetic diversity of the pathogen and their widespread distribution among host species across the growing regions play an important role in determining and devising the control strategies to efficiently control the diseases in the more effective way.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the management of S. sclerotiorum borne disease is not much easy because of its widespread existence, irregular incidence, and the long-term survival by producing huge numbers of sclerotia in the soil. Although several control measures like chemical and cultural methods have been devised and adopted for countering the Sclerotinia stem rot menace (Rousseau et al, 2007) none of them were found fully effective in preventing either the process of disease infection or pathogenesis progression after infection. The extent of genetic diversity of the pathogen and their widespread distribution among host species across the growing regions play an important role in determining and devising the control strategies to efficiently control the diseases in the more effective way.…”
Section: Introductionmentioning
confidence: 99%
“…However, these products need to be applied yearly to obtain the best efficacy and will be unnecessary in the years where climatic conditions are not favorable for disease development. Cultural practices such as crop rotation (Kurle et al, 2001; Rousseau et al, 2007), reduced tillage (Sutton and Peng, 1993; Gracia‐Garza et al, 2002; Mueller et al, 2002), and wide row spacing (Kurle et al, 2001; Mila and Yang, 2008) have been reported to reduce the impact of SSR in soybean fields. The rationale behind these practices is to decrease inoculum and/or maintain unfavorable conditions for fungal development.…”
mentioning
confidence: 99%
“…However, their economical use on a field crop such as soybean remains to be demonstrated. Although some cultural practices such as crop rotation (Kurle et al, 2001; Mitchell and Wheeler, 1990; Rousseau et al, 2007), reduced tillage (Gracia‐Garza et al, 2002; Mueller et al, 2002; Sutton and Peng, 1993), and large row spacing (Mila and Yang, 2008) have been shown to reduce the severity of the disease, the development of resistant varieties is viewed as the most effective control measure and an environmentally attractive alternative (Grau and Hartman, 1999; Steadman, 1979). It has become an important objective in many breeding programs.…”
mentioning
confidence: 99%